Sustainable control of the bird cherry-oat aphid (Rhopalosiphum padi L.) in northwestern Ontario using Beauveria bassiana delivered by bumblebees - Kapongo, Jean Pierre; Kotomale, Morel Libere Comlan; Lubusu, Alphonsine Muzinga Bin; Simo Nana, Romuald; Fopie Tokam, Donald Rostand; Mboussou, Grace Suzert Nottin (Frontiers in Insect Science, 2025)
Rhopalosiphum padi is one of the main vectors of barley yellow dwarf virus (BYDV), which affects the grain yield of oats. Several biological control strategies have been studied to control this pest, one of which is Bee Vectoring Technology (BVT) using bumblebees. We tested the efficacy of Beauveria bassiana, as vectored by bumblebees, and a direct spray application of neem (a natural bio-insecticide derived from the Azadirachta indica tree) on aphids. An assessment of the pest’s impact on the plots surveyed in northwestern Ontario revealed incidence rates of 80%. The use of bumblebees as a dispersal agent of B. bassiana significantly reduced the aphid population (0.542 ± 0.147b) compared to the untreated control (0.125 ± 0.069a). The application of diluted neem also showed a reduction in the aphid population (0.708 ± 0.221a). Although the products used controlled the pests, they had no effect on the aphid’s natural enemy, the ladybug. Therefore, the dissemination of B. bassiana by the bumblebee Bombus impatiens leads to a decrease in the vector Rhopalosiphum padi population and consequently reduces the severity of barley yellow dwarf disease in oat fields.